2015
DOI: 10.2214/ajr.14.12778
|View full text |Cite
|
Sign up to set email alerts
|

Renal Perfusional Cortex Volume for Arterial Input Function Measured by Semiautomatic Segmentation Technique Using MDCT Angiographic Data With 0.5-mm Collimation

Abstract: Weight-adjusted perfusional cortex volume for arterial input function can be measured clinically and may replace renal DTPA scanning using the modified Gates method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…This value is consistent with, although somewhat lower than previous reports of cortical volume of approximately 90 to 120 cm 3 per kidney 3,4,7 . Previous studies have shown that a range of factors influence cortical volume including age, gender, renal function, diabetes, hypertension, body size, and renal morphological parameters 3,4,6,7,13,14 . In this study, we tried to produce a model by applying these factors as candidate explanatory variables for cortical volume.…”
Section: Discussionmentioning
confidence: 99%
“…This value is consistent with, although somewhat lower than previous reports of cortical volume of approximately 90 to 120 cm 3 per kidney 3,4,7 . Previous studies have shown that a range of factors influence cortical volume including age, gender, renal function, diabetes, hypertension, body size, and renal morphological parameters 3,4,6,7,13,14 . In this study, we tried to produce a model by applying these factors as candidate explanatory variables for cortical volume.…”
Section: Discussionmentioning
confidence: 99%
“…Because of advances in multidetector computed tomography (MDCT) technology, more than 64 rows of scanning enable faster acquisition of volumetric image data with superior z-axis resolution with a thin collimation for CT angiography. Compared to complicated and time-consuming manual volumetric assessment as the plotting contour method, automatic or semiautomatic segmentation using various postprocessing techniques can greatly reduce the required time and increase the potential accuracy of measurement [7]. Recently, we found that curved planar reformations (CPR), found by using MDCT angiographic data, which allow the demonstration of plaques with attenuation-dependent color codes, can be applied to the measurement of plaque volume [8].…”
Section: Introductionmentioning
confidence: 99%
“…Chatzikonstantinou et al [ 8 ] reported that 64-row MDCT angiography could detect more plaques in a grading system throughout the aortic arch compared to TEE. Volumetric data acquired with a thinner collimation is expected to provide more accurate volume measurement [ 9 ]. Curved planar reformations (CPR) which allow a single two-dimensional image display of structures that run through multiple oblique planes have been reported to be useful in evaluating the regional calcified plaque condition of the coronary artery [ 10 ].…”
Section: Introductionmentioning
confidence: 99%